Taxonomic significance of morphological and elemental characteristics of achenes of Artemisia genus from Turkey - Karaismailoglu, Mehmet Cengiz; Polat Alkan, Nagihan; Kursat, Murat; Civelek, Semsettin (Wiley, 2024)
In the study, the achene macromorphological and micromorphological characters of the genus Artemisia distributed in Turkey have been researched with the target of knowing systematically important carpological structures for the examined species. Macro-morphological structures of the achenes including color, shape, dimension, and carpopodium diameter were studied with 100 achenes of 10 specimens per taxa with a Light Microscope. Micro-morphological features of the achenes containing surface ornamentation, anticlinal and periclinal cell walls, epidermal cells, and the presence of secondary structures were examined with a Scanning Electron Microscope. EDS analyses were performed with a SEM. EDS analyses were carried out by selecting the same spot on the sample surface at 80 sec under 30 mu m aperture size, with 20 kV acceleration voltage, 8 mm operating distance, high current, and processing time conditions. The color, shape, and dimension of achene have macro-morphologically shown variations. The examined achenes are separated into four shapes; fusiform-oblong, oblong, oblong-ovate, and ovate. Oblong-ovate is the most common type. Achene dimensions range from 0.62 to 2.48 mm in length, and from 0.30 to 1.21 mm in width. Also, carpopodium diameter varies between 0.10 and 0.19 mm. Achene surfaces of the examined taxa are micro-morphologically assessed, and substantial differences are noticeably detected on behalf of the surface structures for instance, surface ornamentation, anticlinal and periclinal cell walls, epidermal cells, and the presence of secondary structures of the achenes. Surface ornamentation is separated into 10 types: irregularly sulcate, regularly sulcate, ruminate, sulcate-scalariform, rugose, favulariate, slightly sulcate, alveolate, tuberculate, and reticulate. A percentage comparison of the elements in the achene pericarp of the studied taxa has been performed with SEM-EDS. Accordingly, pericarps in taxa include C, Ca, K, Mg, Cl, Si, Na, and S elements. In the taxonomy of the genus Artemisia, the achene morphological characters are very significant characteristics that disclose inter-specific relations among the examined taxa. Moreover, a dichotomous key is offered for the identification of the studied taxa based on achene characters.
Keywords: Artemisia; cypsela; EDS; SEM; Turkey